Going to the Great Northern Wilderness: A Scientific and Curriculum-Based Analysis of Premium Study-Tour Route Design under the “Hundred Routes, Hundred Courses” Initiative—— A Case Study of the Xingkai Lake Study-Tour Practice Education Camp Route in Mishan City, Heilongjiang Province - Yanlin Song (Education Research on Study Tours and Practice, 2026)
Against the backdrop of the comprehensive advancement of the “Hundred Routes, Hundred Courses” initiative and the continuous deepening of the “Walking Ideological & Political Class,” study-tour route design has moved beyond traditional sightseeing models and evolved into a systematic, curriculum-based educational product that integrates moral cultivation, interdisciplinary core competencies, in-depth experience, and research-based learning. Taking the premium route “Carrying Forward the Great Northern Wilderness Spirit: Cultivating Souls on the Road” in Mishan City, Heilongjiang Province as a representative case, this paper analyzes its design logic, practical features, and optimization paths from four dimensions: resource endowment, educational objectives, implementation paths, and evaluation systems. The study finds that the route systematically integrates regional resources through a “Five-Color Study Tour” framework, builds a safe and efficient operation system with a “Camp-Hub + Radiating Network” model, and drives the curriculum transformation of study-tour activities through three-dimensional objectives, effectively achieving deep integration of “travel” and “learning.” However, there is still room for improvement in driving independent inquiry, strengthening interdisciplinary task design, refining whole-process evaluation, and empowering with digital technologies. This paper extracts core principles for scientific planning and curriculum construction, forming a replicable practical paradigm that provides theoretical reference and practical insight for the high-quality development of red-themed, ecological, and labor-oriented study tours in Heilongjiang and across China.